2005
DOI: 10.1007/s10147-005-0482-0
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel in patients with CAP-resistant advanced or recurrent endometrial carcinoma: a series of four patients

Abstract: We evaluated the feasibility of weekly paclitaxel in patients with recurrent or advanced endometrial carcinoma who had failed treatment with cyclophosphamide, doxorubicin, and cisplatin (CAP). We treated four patients with CAP-resistant recurrent or advanced endometrial carcinoma with paclitaxel. Paclitaxel (80 mg/m(2); infused over 1 h) was administered weekly for a maximum of 18 weeks, unless disease progression or intractable toxicity developed. A complete response was observed in one patient and a partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…[25][26][27] Two more recent preliminary studies of weekly 1-h paclitaxel infusion in patients with recurrent endometrial cancer have shown response rates of 67% and 75%, but in small numbers (6/9 and 3/4, respectively) of patients. 24,28 Because response in fi rst-line therapy is often double that in second-line therapy, the present series response rate of 26.7% compares favorably with these recent reports.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[25][26][27] Two more recent preliminary studies of weekly 1-h paclitaxel infusion in patients with recurrent endometrial cancer have shown response rates of 67% and 75%, but in small numbers (6/9 and 3/4, respectively) of patients. 24,28 Because response in fi rst-line therapy is often double that in second-line therapy, the present series response rate of 26.7% compares favorably with these recent reports.…”
Section: Discussionsupporting
confidence: 86%
“…[14][15][16][17] In addition, more recent studies have reported that similar regimens (60-100 mg/m 2 per week) continue to be well tolerated and have an improved therapeutic index even in patients with advanced ovarian, endometrial, and breast cancers. 18,19,[21][22][23][24] Several fi rst-line phase II studies of paclitaxel in disseminated endometrial cancer reported overall response rates of up to 30%. [25][26][27] Two more recent preliminary studies of weekly 1-h paclitaxel infusion in patients with recurrent endometrial cancer have shown response rates of 67% and 75%, but in small numbers (6/9 and 3/4, respectively) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence our study populations were more likely to be homogenous. Other platinum-resistant carcinomas which have been treated with paclitaxel based salvage therapy include testicular [144][145][146][147] , NSCLC 148,149 , urothelial 150 , bladder 151 and endometrial carcinomas 152 .…”
mentioning
confidence: 99%